Conhecimento tradicional do potencial do cacho de açaí para a produção de adubo orgânico na comunidade Rio Maiauatá, município de Igarapé-Miri/baixo Tocantins, Pará - SANTOS, Márcia Bianca Souza dos (2019)
The present paper deals with an alternative for the small producers of the familiar agriculture that does not have their needs of buying and selling from other places. It is worth mentioning that besides the low cost is a sustainable source of produce without the environment. Thus, it is intended to show how the study makes the bunch of the açaíseiro can be used as an organic fertilizer aiming at the sustainability of the community in which a research was carried out. Methodology used in the research was carried out in the city of Rio Maiauatá, in the municipality of Igarapé-Miri / PA / Brazil, from January to 2018, and developed on two slopes, a first one characterized by a bibliographical research with systematized studies, based on books published in books, magazines, leaflets and technical information. In addition, the Institute of Geography and Statistics and an Undersecretary of Agricultural and Fisheries Development can not be used as a profiteer of extractivism, not discarding it in nature. What is it that is capable of self-displacement as a research process on the bunch decomposition, is carried out from applications of questionnaires with farmers and a technique that makes feasible The process of decomposition of the bunch for its use as fertilizer. The technique is from harvesting the material in açaí bunch into small pieces and mashed into a meat grinder or blender. This process is in an elevated position to accelerate the process. It concludes that the procurement process is a satisfactory result, since besides contributing to the environment with this large accumulation of residues, it is undoubtedly a positive alternative for the results that only deposit the results in our studies. plants that took months to show the first signs of decomposition. Therefore, the organic garbage coming from the açai trees can bring harm to the human when discarded in nature without proper care. One of the organic materials is the bunch of açaí, better known in riverside locations such as açaí broom. For some cases it is of no use, since it is another type of fertilizer, which is, ecologically correct, since there is a quantity of organic material in nature.